The Impact of Flashcard Educational Media on the Independence of personal Hygiene Among Children with Intellectual Disabilities at SLB Negeri 1 Padang 2024 - Novria Hesti; Sevilla Adriejha; Dian Furwasyih (Rajaki of Tulip Medika Publisher, 2025)
In Indonesia, personal hygiene rates range from 60-80%, with 24% of deaths among children aged 9-12 years attributed to poor personal hygiene. This study aims to determine the impact of educational flashcards on the independence of personal hygiene among children with intellectual disabilities at SLB Negeri 1 Padang. The research was conducted at SLB Negeri 1 Padang from January to August 2024, with data collected on June, 11-12, 2024. The sample consisted of 13 respondents, selected through purposive sampling via observation using a checklist. Data processing involved data editing, coding, entry, and cleaning. Univariate analysis was used to obtain average descriptions of variables, and bivariate analysis using the Mann-Whitney test was employed to determine the effect or relationship between variables. Based on statistical testing using the Mann-Whitney test, there is an effect of educational flashcard on the independence of personal hygiene among children with intellectual disabilities, with a p-value of 0.001 (≤0.05) at SLB Negeri 1 Padang in 2024. It is hoped that educational institutions will provide personal hygiene education to children with intellectual disabilities and develop other educational media for future researchers.